Pengembangan Modul Digital Berbasis Google Sites pada Materi Sistem Pertahanan Tubuh Kelas XI: (Developing Digital Module Based Google Sites for Material Immune System for 11th Grade of Senior High School) - Camilla Masyita Yusha; Listika Yusi Risnani (BIODIK, 2023)
This research aims to produce a valid and practical web-based digital module (using Google Sites) for the topic of the immune system for the eleventh grade of senior high school. This study is a Development Research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used was a questionnaire. The data collection technique for this research was in the form of a questionnaire. The data obtained were analyzed using the quantitative descriptive analysis technique. The research results show that the developed web-based digital module on Google Sites received a "excellent" assessment from subject matter experts, media experts, teachers, and students. This module is proven feasible to be used as an effective learning tool in studying the immune system topic in Biology. The validity evaluation indicates that the assessment by subject matter experts obtained a total score of 3.89 (very good). In contrast, the assessment by media experts obtained a total score of 3.65 (very good). The practicality evaluation from regular school teachers received a total score of 3.75 (very good), and boarding school teachers received a total of 3.85 (very good). The assessment results from regular and boarding school students received a total score of 3.75 (very good). In conclusion, this web-based digital module product (using Google Sites) has been successfully developed and considered feasible as a learning tool for the Biology topic of the immune system for eleventh-grade senior high school. Based on this conclusion, further research is needed to determine the module's effectiveness in Biology teaching. Key words: Biology, Google Sites, Digital Module, Development Research, Immune System Â  ABSTRAK Penelitian ini bertujuan untuk menghasilkan modul digital berbasis web (google sites) yang valid dan praktis pada materi sistem pertahanan tubuh kelas XI SMA. Penelitian ini merupakan Penelitian Pengembangan (Development Research) dengan mengadopsi model ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Instrumen yang digunakan adalah angket. Teknik pengumpulan data dalam penelitian ini dalam bentuk angket. Analisis data yang diperoleh pada penelitian ini dianalisis menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa modul digital berbasis web google sites yang telah dikembangkan mendapat penilaian "sangat baik" dari ahli materi, ahli media, guru, dan peserta didik. Modul ini terbukti layak digunakan sebagai media pembelajaran yang efektif dalam mempelajari materi sistem pertahanan tubuh pada pelajaran Biologi. Uji validitas menunjukkan bahwa penilaian oleh ahli materi memperoleh skor total 3.89 (sangat baik), sementara dari ahli media memperoleh skor total 3.65 (sangat baik). Evaluasi kepraktisan dari guru sekolah reguler memperoleh skor total 3.75 (sangat baik) dan dari guru sekolah asrama memperoleh skor total 3.85 (sangat baik). Hasil uji penilaian dari peserta didik sekolah reguler dan asrama sama-sama memperoleh skor total 3.75 (sangat baik). Dapat disimpulkan bahwa produk modul digital berbasis web (google sites) ini telah berhasil dikembangakan dan layak digunakan sebagai modul pembelajaran Biologi materi sistem pertahanan tubuh kelas XI SMA untuk materi sistem pertahanan tubuh. Berdasarkan kesimpulan tersebut perlu adanya penelitian lebih lanjut untuk mengetahui keefektifan modul dalam pembelajaran Biologi. Kata kunci: Biologi, Google Sites, Modul Digital, Penelitian Pengembangan, Sistem Pertahanan Tubuh